The Impact of a Nurse-Led Physical Activity Program on Reducing Obesity and Enhancing Quality of Life Among Obese Adolescents: A Randomized Controlled Trial - Baby Ilavarasi Chakkaravarthi; Theranirajan Ethiraj; Shankar Shanmugam Rajendran; Kannan Kasinathan; Johnson Chinnadurai; Thillainayaki Chandran; Rathiswari Posan (Journal of Pharmacy and Bioallied Sciences)
Introduction: Physical activity programs effectively reduce obesity and raise awareness of its consequences. Engaging in 30 minutes of daily exercise helps prevent chronic illnesses like diabetes, leading to lower body fat and improved quality of life for obese adolescents. Aim: This study evaluates the impact of a nurse-led physical activity program on obesity reduction and quality of life enhancement among adolescents. Methods and Materials: A quantitative randomized control study was conducted at Choolaimedu Higher Secondary School, Chennai, involving 100 adolescents aged 12–14 years. Data were collected using the Physical Activity Questionnaire (PAQ-A) and Pediatric Quality of Life Inventory (PedsQL). Pre and posttest scores were analyzed using paired t-tests and Chi-square tests. Results: The sample included 18 females and 32 males. The experimental group showed a 31.20% physical activity gain score and a 25.63% quality of life gain score, compared to 14.26% and 2.03% in the control group, respectively. Conclusion: Structured physical activity programs significantly reduce obesity and enhance quality of life, warranting further research on their long-term effects and optimal structures.